2019
DOI: 10.1128/aac.02530-18
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Bedaquiline Resistance in Treatment-Naive Tuberculosis Patients and Verapamil Effectiveness

Abstract: In the regions where bedaquiline (BDQ) is introduced into the regimen, analysis of MIC and screening for preexisting resistance mutations could be crucial. The high prevalence of isolates with high BDQ MICs without prior exposure to BDQ was worrisome. It was also concluded that efflux pumps play a pivotal role in intrinsic BDQ resistance; therefore, the potential of verapamil as an adjunctive therapy to combat BDQ resistance should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 22 publications
3
40
1
Order By: Relevance
“…This work provides a summarized panel of mutations linked to DLM and BDQ resistance detected through WGS. DLM and BDQ are currently distributed in a limited number of countries [62,63]; however, RAM in BDQ naïve Mtb strains have been already identified [30,35,37]. The latter suggests that BDQ/DLM Mtb-resistant strains could be circulating even in countries where these drugs have not been introduced yet.…”
Section: Discussionmentioning
confidence: 99%
“…This work provides a summarized panel of mutations linked to DLM and BDQ resistance detected through WGS. DLM and BDQ are currently distributed in a limited number of countries [62,63]; however, RAM in BDQ naïve Mtb strains have been already identified [30,35,37]. The latter suggests that BDQ/DLM Mtb-resistant strains could be circulating even in countries where these drugs have not been introduced yet.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that the most spreading mechanism of BDQ resistance in clinical setting is represented by mutations in Rv0678 gene even if with a low level of BDQ-resistance (Villellas et al, 2017;Nieto Ramirez et al, 2020). To fight BDQ-resistance caused by Rv0678 mutations and to allow its use for the largest possible part of patients, verapamil, an efflux inhibitor, could be the keystone, since it has been demonstrated to increase the efficacy of BDQ against both M. tuberculosis and Mycobacterium abscessus (Ghajavand et al, 2019;Viljoen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As responsible for BDQ resistance, mutations in the intergenic region between Rv0678 and MmpS5 as well as mutations in the genes encoding the efflux pump MmpS5/MmpL5 were also reported (Ghajavand et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium antagonists improved in vitro activities of tetracycline and fluoroquinolones against S. aureus, Enterobacteriaceae and non-fermenters irrespective of whether the strains were tetracycline-or fluoroquinolone-resistant [158][159][160]. It also improved activities of ofloxacin, rifampicin, and bedaquilin, but not isoniazid or amikacin against M. tuberculosis as well as M. abscessus (Table 3) [ [161][162][163][164][165][166][167][168][169]. Verapamil also increased the intraphagocytic activities of isoniazid and rifampicin [168] as well as bedaquilin and moxifloxacin [168] against drug-susceptible and drug-resistant M. tuberculosis and also the intracellular activity of azithromycin against L. monocytogenes [170,171] and that of daptomycin against S. aureus [172].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%